Seismic structure of West Africa by surface wave tomography - (:unkn) unknown (My University, 2019)
This thesis allowed us to produce group velocity maps of the fundamental mode of Rayleigh waves, using both earthquakes and seismic ambient noise correlation. In this study, in addition to the damped least squares method, we adapted for the very first time a new inversion method, called SOLA-Backus-Gilbert in regional context. At short periods, the group velocities maps exhibit fast velocities for the oceanic crust and slow velocities for the continental crust. For the intermediate periods, the Taoudeni Basin is characterized by low velocities compared to the rest of the west african craton due to the thickness of the sedimentary layer. Over long periods, the roots of the Man-Leo and Reguibat shields are characterized by fast velocities, showing a cold and thick lithosphere under the craton, while we found slow group velocities under the Pan-African orogenic belts zones indicating a thin lithosphere.
Keywords: African Research